2020
DOI: 10.1093/infdis/jiaa575
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Aerosolized Severe Acute Respiratory Syndrome Coronavirus 2 Among Hospitalized Coronavirus Disease 2019 Patients

Abstract: During April and May 2020, we studied 20 hospitalized COVID-19 patients, their hospital rooms (fomites and aerosols), and their close contacts for molecular and culture evidence of SARS-CoV-2 virus. Among the more than 400 samples, we found molecular evidence of virus in most sample types, especially the nasopharygeal (NP), saliva, and fecal samples, but the prevalence of molecular positivity among fomites and aerosols was low. The agreement between NP swab and saliva positivity was high (89.5%, Kappa 0.79). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 26 publications
1
76
1
Order By: Relevance
“…Indeed, a better understanding of viral resistance to airborne stress is key to estimating infectious risk. Three published studies (103)(104)(105) included viral cultures from air samples, all of which were negative; however, the Santarpia et al study (103) observed indirect signs of viral replication in two of their samples, including a mild cytopathic effect upon microscopic inspection after 3 to 4 days. On the other hand, in two unpublished studies, Santarpia Western blotting to yield interesting results.…”
Section: Air and No-touch Surface Samplingmentioning
confidence: 99%
“…Indeed, a better understanding of viral resistance to airborne stress is key to estimating infectious risk. Three published studies (103)(104)(105) included viral cultures from air samples, all of which were negative; however, the Santarpia et al study (103) observed indirect signs of viral replication in two of their samples, including a mild cytopathic effect upon microscopic inspection after 3 to 4 days. On the other hand, in two unpublished studies, Santarpia Western blotting to yield interesting results.…”
Section: Air and No-touch Surface Samplingmentioning
confidence: 99%
“…After further screening and supplementary searching of articles published or posted between January 1 and October 27, 2020, we identified an additional article, and a total of 24 articles were included in the review ( Figure 1 ). 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 included studies, all were cross-sectional observational studies. Ten studies (41.7%) were from China, [9][10][11]15,[18][19][20]22,25,29 and the remaining were from the United States (4 [16.7%]), 12,13,26,30 Hong Kong (2 [8.3%]), 14,21 Korea (2 [8.3%]), 24,27 Singapore (2 [8.3%]), 3,16 Iran (2 [8.3%]), 8,28 the United Kingdom (1 [4.2%]), 19 and Italy (1 [4.2%]). 23 Of all included articles and studies, 20…”
Section: Characteristics Of Included Articles and Studiesmentioning
confidence: 99%
See 2 more Smart Citations